Design and Performance of 1.5-Meters Radius Wind Turbine under High Wind Speeds Condition - Dahham, A.; Kassenov, A.; Abishev, K. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2023)
Global warming is a serious challenge to civilizational development due to the increase in temperature because of exhaust gases. These gases, produced by burning fossil fuels, should reduce or replace the way energy is generated using renewable energy sources. Our study shows the ability of 1.5-meter reduce wind turbine to create a mechanical power to drive some mechanical devices under high wind speed conditions. This type of devices needs approximately 1460 watt (2 horses); the turbine designed with angle blade Beta 2 degrees and Lambda 10 to reach maximum benefit from the wind. The turbine is exposed to variable wind, as a result, the turbine generates the required power when the wind speed is from 9.3 to 9.7 m/s, when the generated power is less than the required one, the device can work with less efficiency, and more power is better within the limits that do not damage device.